Boosting Photoresponse Performance and Stability of Photoelectrochemical Photodetectors by Chemical Bath Depositing Multilayer MoS2 on ZnO Electrode - Jingyao Ma; Jiawei Wang; Xin Shi; Tianqi Sun; Pengpeng Dai (Nanomaterials)
ZnO nanorods are promising nanomaterials for photoelectrochemical photodetectors (PEC PDs). However, the weak photocurrent density, delayed response, and low stability of ZnO are major drawbacks for their applications. To address these challenges, we integrated multilayer MoS2 nanosheets with ZnO nanorods using a chemical bath deposition method. The resulting ZnO/MoS2 heterojunction achieved a photocurrent density of 1.02 mA/cm2 (~20 times higher than that of bare ZnO), ultrafast response times (90/150 ms), and 92% stability retention over 3600 s. These enhancements originated from suppressed charge recombination and accelerated water oxidation kinetics. Our work provides another possible energy-saving route toward developing high-efficiency and stable ZnO-based photoanodes for practical applications in PEC PDs.